(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In day-to-day life, people with hearing impairment feel discomfort in public areas. They can’t explain their words to others. So, Sign language recognition comes. Sign Language recognition has many applications and increasing continuously. This paper shows the CNN model of a hand sign-detection system converting it into a message. From the existing designs which are based on image processing, showing a simple single letter, it can make a complete message by joining the all-single letter. The predicted message is displayed on a side screen.